2016
DOI: 10.1088/0967-3334/37/2/227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart disease and calibration interval on accuracy of pulse transit time–based blood pressure estimation

Abstract: Continuous blood pressure (BP) measurement without a cuff is advantageous for the early detection and prevention of hypertension. The pulse transit time (PTT) method has proven to be promising for continuous cuffless BP measurement. However, the problem of accuracy is one of the most challenging aspects before the large-scale clinical application of this method. Since PTT-based BP estimation relies primarily on the relationship between PTT and BP under certain assumptions, estimation accuracy will be affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…The estimation errors were significantly higher in hypertensive subjects for all those methods. This is in agreement with our earlier study 21 , which showed that the overall accuracy of SBP estimation was significantly lower in subjects with hypertension and heart diseases than in healthy subjects. However, except for the evidence that the SD of the estimation errors of PTT#3-PTT#6 went beyond 8 mmHg in hypertensive group, all the other estimations error biases and SD were within 5 ± 8 mmHg.…”
Section: Discussionsupporting
confidence: 94%
“…The estimation errors were significantly higher in hypertensive subjects for all those methods. This is in agreement with our earlier study 21 , which showed that the overall accuracy of SBP estimation was significantly lower in subjects with hypertension and heart diseases than in healthy subjects. However, except for the evidence that the SD of the estimation errors of PTT#3-PTT#6 went beyond 8 mmHg in hypertensive group, all the other estimations error biases and SD were within 5 ± 8 mmHg.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that the modified transmission of pulse waves in arteries experiencing disease-induced structural and functional changes is a potential confounding factor. The finding of decreased PTT-BP accuracy in patients with heart disease was also confirmed by Spiesshofer et al [32] and Ding et al [22].…”
Section: Reporting Of Patient Demographicssupporting
confidence: 66%
“…Of the 73 studies that reported correlation results, 22 met this criterion. Three studies [21][22][23] included in this analysis reported the coefficient of determination (r 2 ) instead of r. To include these studies, we used the square root (r) of this value. On a few occasions, studies did not report an overall mean error or r and instead reported multiple values of each population they tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations